Genetic variants identified in children with recurrent infections - A. S. Levina; E. N. Suspitsin; N. V. Skripchenko; O. V. Goleva; O. M. Ibragimova (LLC "Diagnostics and Vaccines", 2021)
Currently, the most effective way to diagnose hereditary defects of the immune system is molecular genetic research, the results of which are evaluated in conjunction with the data of clinical and laboratory studies.Aims of the sudy: to evaluate the frequency and spectrum of rare genetic variants associated with the development of primary immunodeficiency (PID) in children with recurrent infections.Materials and methods: DNA samples from 113 children with recurrent infections were analyzed by targeted multigene sequencing of 338 PID-associated genes. Results: Pathogenic variants appropriate to the potential diagnosis of PID were identified in 8% of patients. Interestingly, 47.8% of children had variants associated with auto-inflammatory disorders.